Early-Life Exposure to Clostridium leptum Causes Pulmonary Immunosuppression. - Fei Huang; Hong-Mei Qiao; Jia-Ning Yin; Yang Gao; Yang-Hua Ju; Ya-Nan Li (PLoS ONE, 2015)
Low Clostridium leptum levels are a risk factor for the development of asthma. C. leptum deficiency exacerbates asthma; however, the impact of early-life C. leptum exposure on cesarean-delivered mice remains unclear. This study is to determine the effects of early-life C. leptum exposure on asthma development in infant mice.We exposed infant mice to C. leptum (fed-CL) and then induced asthma using the allergen ovalbumin (OVA).Fed-CL increased regulatory T (Treg) cells in cesarean-delivered mice compared with vaginally delivered mice. Compared with OVA-exposed mice, mice exposed to C. leptum + OVA did not develop the typical asthma phenotype, which includes airway hyper-responsiveness, cell infiltration, and T helper cell subset (Th1, Th2, Th9, Th17) inflammation. Early-life C. leptum exposure induced an immunosuppressive environment in the lung concurrent with increased Treg cells, resulting in the inhibition of Th1, Th2, Th9, and Th17 cell responses.These findings demonstrate a mechanism whereby C. leptum exposure modulates adaptive immunity and leads to failure to develop asthma upon OVA sensitization later in life.